An Analysis On English Textbook Pathway To English For The First Year Student Of Senior High School Based On 2013 Curriculum - Agus Prasetyo Nugroho, Mr. Alief (2016)
This study is about textbook analysis. Theobjective of this research is to reveal whether the book is in accordance with the existing curriculum, the book entitled Pathway to English created by Th. Grace M. Sudarwati and Eudia published by grants in 2013. The object of this study is the materials inPathway to English Th. M. Sudarwati and Eudia Grace. This study uses data comparison. This study uses qualitative research. In this study, there are two types of data source, is secondary data and primary data. The primary source of data is the handbook itself while secondary data are other materials related to this research. The data are collected through literature study and analysis of data with descriptive data. The results is, based on the analysis of stucture, Pathway to English is the student handbook, the book includes material that is consistent and commensurate with the 2013 Curriculum. The results showed that this book is not compatible with the 2013 Curriculum.